Uji sensori Mi Basah Bebas Gluten (Gluten Free) berbasis Tepung Sukun dengan Penambahan Karagenan - Kristiningsih, Ari; Wittriansyah, Khoiruddin; Purwaningrum, Santi (JURNAL AGROINDUSTRI HALAL, 2022)
Breadfruit is one of the alternative sources of new carbohydrates in the form of wet noodles. Breadfruit flour is a gluten-free food product, which is good for digestion and also for children with autism. Carrageenan is added to the manufacture of noodles as a substitute for gluten in the dough. To add color and taste, squid ink is added as a natural dye for breadfruit noodles. This study aims to determine consumer acceptance of breadfruit flour-based wet noodles with the addition of carrageenan as a thickener and squid ink as a dye. This study used a completely randomized design (CRD) with five treatments, namely with the addition of carrageenan 1%, 3%, 4%, 5% and without the addition of carrageenan (0%). Based on the results of the study, it was found that the water content of breadfruit flour was 2.86%, ash content was o, 2% and protein content was 6.35%. Based on the sensory test, it was found that the P value > 0.05 on all parameters, namely color, taste, aroma and texture, which means that the difference in carrageenan concentrations is not significantly different. The most preferred color by panelists on noodles with the addition of 7% carrageenan. The most preferred taste in breadfruit noodles without the addition of carrageenan and 5%. The most preferred aroma in noodles with the addition of 5% carrageenan. The most preferred texture in noodles with the addition of 1% carrageenan.